THE LATE MEDIEVAL DEBATE ABOUT THE NATURE OF PHENOMENAL REALITY IN FRANCISCAN THEOLOGY AND ISLAMIC THOUGHT AND ITS GREEK SOURCES. - Bychkov, Oleg (Revista Española de Filosofía Medieval, 2024)
The tendency to question the accuracy of sensory perception is found in various medieval theological traditions, including Franciscan and Islamic. In both these traditions, the source of the idea that we cannot trust our sensory perception seems to have been the Greek commentaries on Aristotle. However, both traditions go beyond ideas contained in Greek Aristotelian literature and independently develop similar arguments and come to similar conclusions about the reliability of sensory perception.